Chitosan—PRP nanosphere as a growth factors slow releasing device with superior antibacterial capability. (13th June 2018) - Ikono, Radyum; Mardliyati, Etik; Agustin, Iis Tentia; Ulfi, Muhammad Mufarrij Fuad; Andrianto, Dimas; Hasanah, Uswatun; Bachtiar, Boy Muchlis; Mardianingsih, Nofa; Bachtiar, Endang Winiati; Maulana, Nurwenda Novan; Rochman, Nurul Taufiqu; Xianqi, Li; et al.
Abstract: A new way to administer platelet-rich plasma (PRP) to improve its viability in more complex and chronic wound healing and soft/hard tissue regeneration in alveolar ridge preservation is demanded. In this study, PRP was encapsulated in chitosan to form a nanosphere with size below 100 nm with an idea to prolong PRP's growth factors release. Chitosan nanosphere was prepared by ionic gelation method, while PRP was encapsulated by inclusion method. Morphology analysis by transmission electron microscope (TEM) showed that PRP was encapsulated efficiently in the chitosan matrix, making a spherical shape with size of 30–80 nm. Particle size analysis by dynamic Light Scattering (DLS) method further showed that the average size of chitosan—PRP nanosphere was 51.27 ± 33.75 nm, which is a good indication for biomaterials used in body. The stability of the nanoparticle colloid was confirmed with zeta potential score of 50.42 mV. 200 μ l encapsulation of PRP in chitosan nanosphere had the highest encapsulation efficiency, that was further used in total protein release analysis in phosphate buffered saline (PBS) solution. It started with initial burst at 7 h, followed by steady release, then 'quasi-plateau' after 96 h (at around 60%), dominated by Korsmeyer-Peppas kinetics model and Fick's diffusion mechanism. Finally, the nanosphere showed an excellent antibacterial activity against S. mutans as shown from 90.63% bacteria inhibition during assay. The results showed that chitosan—PRP nanosphere could be used as a novel approach for complex/chronic wound healing and soft/hard tissue regeneration following periodontitis treatment or tooth extraction that needs prolonged growth factor release.